Protective Effect of Acacia Ferruginea Bark Extract against Paracetamol-Induced Nephrotoxicity in Rats - Divyashree R; Chandrashekhar M Sultanpur (RGUHS Journal of Pharmaceutical Sciences)
Background Paracetamol-induced nephrotoxicity is associated with oxidative stress and kidney damage. This study explores the potential of Acacia ferruginea bark extract as a protective agent against nephrotoxicity.Objectives This study aims to examine the preventive effects of A. ferruginea bark extract against paracetamol-induced nephrotoxicity in rats.Methods The bark of A. ferruginea was collected shade-dried and extracted with ethanol using the Soxhlet method. The nephroprotective effects of the ethanolic extract of A. ferruginea bark EEAFB were assessed in a rat model of paracetamol-induced nephrotoxicity. Physical parameters such as body and kidney weight biochemical markers including serum urea uric acid creatinine blood urea nitrogen BUN and TSP were measured. Histopathological examination of kidney tissues was conducted to confirm the nephroprotective effects. Antioxidant activity was further evaluated through lipid peroxidation LPO and reduced glutathione GSH levels were reduced.Results In this model EEAFB at 200 mgkg and 400 mgkg significantly Plt 0.001 protected against nephrotoxicity by normalizing serum biomarkers reducing LPO levels and increasing GSH levels.Conclusion The study indicates that EEAFB is a potent nephroprotective agent with strong antioxidant properties potentially beneficial against drug-induced nephrotoxicity.